Intervention with students in social and family risk. (Journal of Parents and Teachers, 2013)
This paper is a presentation of a practical project that we are carrying out with students that are in psychologic/social/familial risk in the Colegio Claret de Segovia. We explain how to start with this project, how is the group of professionals that take care of children formed and what are the most significant interventions with these students with whom all the measures of attention to diversity are almost finished.
Keywords: Social or familial risk; Educators; Group; School.